Application of pre-participation cardiovascular screening guidelines to novice older runners and endurance athletes - Justin R Abbatemarco; Courtney Bennett; Adrian J Bell; Laura Dunne; Martin E Matsumura (SAGE Open Medicine, 2016)
Objectives: Despite robust growth in participation in marathons and endurance sports among older individuals, guidance regarding pre-participation cardiovascular evaluation of these athletes is lacking. The objective of this study was to assess the utility of currently available pre-participation cardiovascular evaluation guidelines as applied to a cohort of older novice endurance athletes. Methods: We applied data from 1457 novice runners and endurance athletes aged 35 years and older to two pre-participation screening tools, the American Heart Association/American College of Sports Medicine Pre-Participation Questionnaire and the 2001 Working Group recommendations for pre-participation screening of masters athletes (2001 Masters). Results: Application of the American Heart Association/American College of Sports Medicine Pre-Participation Questionnaire identified 42.1% for which pre-participation cardiovascular evaluation was indicated. Of those who met criteria, 51.5% reported completion of a healthcare evaluation. Application of the 2001 Masters guidelines identified 75.2% who qualified for pre-participation electrocardiogram and 34.0% for pre-participation stress testing. Of those who met 2001 Masters criteria for pre-participation testing, 43.7% and 24.6% underwent recommended electrocardiogram and stress testing, respectively. While there was modest concordance with recommendations for pre-participation evaluations based on both American Heart Association/American College of Sports Medicine Pre-Participation Questionnaire and 2001 Masters, only athlete age was independently associated with completion of a pre-participation healthcare evaluation and only athlete age and athlete’s participation in marathons were independently associated with pre-participation stress testing. Conclusion: Among older novice endurance athletes, application of the American Heart Association/American College of Sports Medicine Pre-Participation Questionnaire and 2001 Masters guidelines identifies a significant percentage of athletes for whom pre-participation evaluation and testing are recommended. Concordance with these guidelines was modest and providers were primarily influenced by athlete age and competitive goals when planning pre-participation testing. Given the rarity of cardiovascular events among older participants in endurance events, the cost-effectiveness of the American Heart Association/American College of Sports Medicine Pre-Participation Questionnaire and 2001 Masters guidelines may be unacceptable for general use.